AGROCLIMATIC ZONING OF THE RIVNE REGION - Voznіuk Nataliya; Sobko, Zoriana (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The article deals with the agroclimatic zoning of the Rivne region, which is divided into northern and southern parts. The northern part of the region actually belongs to the Polissia area, and the southern part is the forest-steppe zone. In the article are described the characteristics of agro-climatic regions, and the specifics of the plant and animal productions are investigated. Also the results of researching of changes in meteorological and meteorological indexes are presented in this paper. Thus, it is established that the territory of the Rivne region, like most of Ukraine and the world territory, is exposed to climate change caused by global warming. The reorientation of agricultural production in the Rivne region due to climate change is revealed.